الحجر على المعوق ذهنيا دراسة على ضوء التشريع الجزائري والعربي المقارن - معيفي, الهادي (جامعة الوادي University of Eloued, 2018)
يعتبر المعوق ذهنيا فاقد الأهلية, لإصابته بخلل عقلي, يؤثر على إرادته, وقدرته على الإدراك والاختيار الصحيح, ومن هنا جاء نظام الحجر في التشريع, لمنع تصرفه في أمواله, وحمايتها وحفظها واستثمارها من طرف الولي, الذي تعينه المحكمة نائبا عنه للقيام بشؤونه, وحماية الغير الذي قد يتعاقد معه, بحسن نية أو لعدم علمه بحكم الحجر. أعطى المشرع الجزائري حق رفع دعوى الحجر لأقارب المعوق ذهنيا، ثم لمن له مصلحة, ثم للنيابة العامة. ويوقع الحجر بموجب حكم قضائي, تصدره المحكمة المختصة, فإذا صدر وتم نشره, فإنّ المعوق ذهنيا يصبح في حكم فاقد الأهلية؛ كالصغير غير المميز والمجنون، وأهم أثر من آثار الحجر أن تصرفاته في أمواله تكون باطلة, ولا تنتج آثارها القانونية في مواجهة الغير, مادامت علة الحجر قائمة, ويرفع الحجر عن المعوق ذهنيا متى زالت أسبابه. Summary A mentally disabled person is considered incapacitated, since he is mentally impaired. This affects his will and ability to perceive and make the right choice. Hence, the quarantine system in the legislation came to prevent him from making any decision concerning his money; in order to protect it and save it. Therefore, it will be invested by the guardian appointed by the court as his deputy to carry out his affairs. It also protects those who may deal with him without being aware of the quarantine verdict. The Algerian legislator gave the relatives of the mentally handicapped person, then those with an interest, and then to the prosecutor the right to litigate. The quarantine verdict is signed and issued by a special ruling court. As a result, if the verdict came out and published, the mentally handicapped person would be considered as ineligible as a child or a mad person. Based on this verdict, he is considered invalid in terms of making any decision about his money. In addition to that, it would not have legal effects against others, since the cause of the quarantine still exists. Henceforth, the quarantine can be dropped when the causes no longer exist.
Keywords: الحجر، المعوق ذهنيا، المقدم ، الولاية، الوصي، حجر تلقائي، حجر قانوني